THE COMPARISON OF THE AFFECTIVE STRATEGIES USED BY DOMESTIC AND INTERNATIONAL UNIVERSITY STUDENTS IN PREPARATORY CLASSES IN TURKEY TO COPE WITH AFFECTIVE FILTER IN SPEAKING ENGLISH VS. THEIR SPEAKING PROFICIENCY - Temel, Merve; Ozkan, Yonca (PEOPLE: International Journal of Social Sciences, 2016)
Accompanied by the newly emerging circumstances and rapidly increasing requirements of the globalizing world, language learning and teaching has always been in the limelight. It is a field in which there are a great number of researches to help learners and teachers overcome hardships and foster their experiences in language. Compared to other skills, speaking in a different language is the most challenging one for learners, which deserves much attention. Along with cognitive, personal, social factors, etc., affective ones like motivation, confidence and anxiety also play a significant role in performing speaking. Individuals learn a language if they have an intelligible input and if their affective filters (AF) are low enough to permit it in. In studies done on this area, learners state that their speaking performances are hindered because a mental block prevents them realizing a good speaking when they feel unmotivated, anxious or insecure. It is therefore important to come up with strategies so as to come to grips with it for both learners and teachers in helping them. This pilot study aims at finding affective variables domestic (Turkish) and international students in preparatory classes of two state universities in Turkey might face in speaking English and exploring different strategies used to lower affective filter and itscorrelation with their achievement through speaking grades. This way, it intends to help learners from both sides see what other strategies are employed by those from a different background, society, culture and nationality for the promotion of speaking, and give insight into their implementations. As a result of the study, which was carried upon 11 domestic, Turkish and 11 international students, it shows that international students have higher values in affective factors like self-confidence, motivation in, and attitude towards speaking English than Turkish students. Likewise, their speaking scores and affective strategy use are ahead of those of Turkish students.